The Nutritional Parameters in Children with Delays in Speech - Sürücü Kara, İlknur and Dolğun, İlke and Mertoğlu, Cuma (Cerrahpaşa Medical Journal, 2025)
Objective: This study aimed to examine and compare the data on nutritional parameters in children with specific language impairments. Methods: Children under 5 years of age who presented to the outpatient clinic with isolated speech delay and were diagnosed with a specific language disorder, along with a healthy control group, were evaluated. The hemoglobin, iron, vitamin B12, and vitamin D levels of the patients were recorded after normal values and deficiency limits were determined for each age group. Results: Of the 188 children, 94 were in the control group and 94 were in the patient group. The control group was the same age and gender as the patients. Seventy-one (75.5%) of the patients were male and 23 (24.5%) were female. The mean age was 2.70 ± 0.65; the median age was 2.66 (min-max: 1.50-3.92) years. The mean serum iron levels in the patient group (67.95 ± 41.86 µg/dL) were significantly lower than in the control group (81.59 ± 37.34 µg/dL) (P = .008). B12 deficiency was significantly higher in the patient group (30%) than in the control group (16%) (P = .037). Other nutritional parameters of the patient and control groups were similar. Conclusion: Low iron levels and vitamin B12 deficiency may be effective factors in speech delay. It is important to the nutritional parameters for speech delay and to treat vitamin deficiencies if present. Cite this article as: Sürücü Kara İ, Dolğun İ, Mertoğlu C. The nutritional parameters in children with delays in speech. Cerrahpaşa Med J. 2025, 49, 0065, doi:10.5152/cjm.2025.24065.